Notary Responsibility for Legal Smuggling in the Issuance of Absolute Deed of Power of Attorney for Sale and Purchase of Land - Rizky Hadiwidjayanti; Liza Prihandhini (Faculty of Law, Universitas Pekalongan, 2023)
This paper analyses the Notary's Responsibility for Legal Smuggling Acts in the Issuance of Absolute Power of Attorney for The Sale and Purchase of Land. In analysis used juridical-normative legal research methods. The data were collected through literature studies and analyzed qualitatively. This study concluded that in the case of the Batulicin District Court Decision Number 06/Pdt.G/2018/PN Bln, a notary named Pang Andreas Pangestu committed an unlawful act because he issued a Deed of Power of Attorney, which was categorized as an Absolute Power of Attorney containing the clauses referred to in the Instruction of the Minister of Home Affairs Number 14 of 1982, which was a form of legal smuggling to avoid obligations and prohibitions that had been regulated in legislation. Therefore, the Power of Attorney Deed was annulled. The Notary, in his position as a PPAT in doing the deed, is burdened with his responsibility. Such duties include criminal, civil and administrative liability. In this case, the Notary can be subject to civil commitment, which is punished with compensation of Rp 1,500,000,000 (one billion five hundred million rupiah) due to unlawful acts committed by him and can be subject to administrative responsibility also because the Notary committed violations in the UUJN, especially Article 16 paragraph 1 letter a.